1957
DOI: 10.1128/jb.73.2.211-217.1957
|View full text |Cite
|
Sign up to set email alerts
|

IMMUNIZATION AGAINST BRUCELLA INFECTION VI.Brucella melitensis

Abstract: The isolation of streptomycin-dependent mutants from different Brucella was suggested by the results of Hall and Spink (1947), and de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Brucellosis control and eradication programs largely depend on vaccines, which have been successfully used worldwide for decades. Three vaccines are used in animals: B. abortus S19 and RB51, and B. melitensis Rev.1 [50][51][52]. They provide effective protection against infection and abortion in animals.…”
Section: Proteomics-based Detection Of Brucella Spp Immunodominant Pmentioning
confidence: 99%
“…Brucellosis control and eradication programs largely depend on vaccines, which have been successfully used worldwide for decades. Three vaccines are used in animals: B. abortus S19 and RB51, and B. melitensis Rev.1 [50][51][52]. They provide effective protection against infection and abortion in animals.…”
Section: Proteomics-based Detection Of Brucella Spp Immunodominant Pmentioning
confidence: 99%
“…The live attenuated Brucella melitensis vaccine strain Rev.1 is recognized worldwide as the best vaccine available against brucellosis in sheep and goats. 10,11,82,83…”
Section: Discussionmentioning
confidence: 99%
“…The live vaccine B. melitensis Rev 1 (Rev 1) is currently utilized for the control of brucellosis in small ruminants. This strain was developed by Herzberg and Elberg in the mid-1950s and retains common characteristics of Brucella but is resistant to streptomycin and susceptible to penicillin G [9]. Subcutaneous or conjunctival immunization with Rev 1 confers protective immunity in small ruminants.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of vaccination programs to improve herd resistance is generally required to control the spread of the disease. To date, Rev 1 is the best available vaccine for the prevention of B. melitensis infection in small ruminants [9] and is typically administered to young animals (3-5 months old) at 0.5-2 × 10 9 colony-forming units (CFU) subcutaneously. Although a bacteremia occurs after vaccination, it has been reported that the vaccine strain is cleared in approximately 14 weeks in goats.…”
Section: Introductionmentioning
confidence: 99%